Deteksi Keragaman Genetik pada Anggrek Dendrobium Mutan secara Morfologi dan Molekuler - Dian Ayu Aprilia (Fakultas Pertanian, 2025)
Colchicine mutations are used to increase plant diversity through induction of polyploidy, which prevents chromosome separation during meiosis. Molecular analysis was performed using PCR (Polymerase Chain Reaction) technology with ISSR primers to distinguish closely related individuals. In addition, ploidy analysis was also performed to count chromosomes in mutant Dendrobium. This study involved 95 mutant orchid plants, consisting of Dendrobium stratiotes and Dendrobium gabriella suryajaya, which were acclimatized and analyzed. The purpose of this study was to detect the diversity of mutant Dendrobium orchid plants morphologically and prove the diversity of Dendrobium orchid plants with clusters and molecular. The observed parameters include plant height, leaf area, leaf color, leaf shape, number of leaves, Root Length, number of roots, stomatal type, and number of chromosomes. Morphological Data were analyzed descriptively quantitatively, while molecular data were analyzed through clustering and dendrograms to determine the value of genetic similarity. The results showed that colchicine mutation treatment resulted in significant morphological and molecular diversity, with the highest genetic similarity value of 98% in some samples and the lowest value of 29%. This research provides important insights into the use of chemical mutations to increase genetic diversity in ornamental plants, particularly orchids.
Reaploud Repository February 2026_Hasyim
Keywords: Genetic analysis; colchicine mutation; PCR (Polymerase Chain Reaction); primary ISSR; chromosome analysis